2012
DOI: 10.1080/02701367.2012.10599848
|View full text |Cite
|
Sign up to set email alerts
|

Expert Anticipatory Skill in Striking Sports

Abstract: Expert performers in striking sports can hit objects moving at high speed with incredible precision. Exceptionally well developed anticipation skills are necessary to cope with the severe constraints on interception. In this papr we provide a review of the empirical evidence regarding expert interception in striking sports and propose a preliminary model of expert anticipation. Central to the review and the model is the notion that the visual information used to guide the sequential phases of the striking acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 79 publications
6
82
0
Order By: Relevance
“…These results suggest that, at the very least, skilled players are likely to use both proximal and distal cues to anticipate the direction of forthcoming shots. This is consistent with a previous study [9] that showed that skilled players fixed their gaze toward the proximal regions of the opponent, probably because the relative motions from the trunk and hip were visible, in order to anticipate the movement of the distal parts (see review for details [11]).…”
Section: Introductionsupporting
confidence: 92%
“…These results suggest that, at the very least, skilled players are likely to use both proximal and distal cues to anticipate the direction of forthcoming shots. This is consistent with a previous study [9] that showed that skilled players fixed their gaze toward the proximal regions of the opponent, probably because the relative motions from the trunk and hip were visible, in order to anticipate the movement of the distal parts (see review for details [11]).…”
Section: Introductionsupporting
confidence: 92%
“…The significant positive correlations found between anticipation scores and selected game batting statistics help further consolidate to a degree the role of advance information outlined in Müller and Abernethy (2012) model. The findings of this study go beyond the highly structured video-based and in-situ studies that were used to develop their model.…”
Section: Discussionmentioning
confidence: 68%
“…Anticipation skill is necessary for the performer (e.g., baseball batter) to cope with several constraints to skill performance imposed by the opponent (e.g., pitcher) such as object velocity, swing, or curve of the object in its flight phase, as well as precision of bat-ball interception based upon the size of the striking implement and the rules of the game that can limit the performer's participation in the game (Müller & Abernethy, 2012). No scientific evidence, however, exists to our knowledge of whether anticipation as measured in structured laboratory based tests is related with "real-world" game performance.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Burroughs also devised an in situ occlusion device to test transfer of laboratory-based learning, which will be discussed further in the baseball training case study. In situ tasks not only are used to validate video-occlusion methods but also are used to study the relationship of perception and coordinated motor actions (e.g., Abernethy, 1984 ; Müller and Abernethy, 2006 , 2012 , 2014 ). For training purposes, adding in situ tasks may make up for the lack of ecological validity in typical video-occlusion laboratory tasks while also leveraging the precision and efficiency of tasks designed to reveal and measure the perceptual skills that underlie the extraordinarily rapid decision making of skilled athletes in many fast-action sports (Williams and Ward, 2003 ).…”
Section: Introductionmentioning
confidence: 99%